Mechanical behaviour of pre-stressed railway sleepers using geopolymer concrete - Khan, S. Imran; Brindha, D.; Panneerselvam, G. (Journal of Structural Engineering, 2024)
Geopolymer concrete can be considered as a green building technology which serves as alternatives for cement and fine aggregate by using Alkaline Activator Solutions (AAS) Fly Ash (FA) Granulated Blast Furnace Slag (GGBS) and Copper Slag (CS) in Geopolymer Concrete (GC). The High Strength Geopolymer Concrete (HSGC) M60 grade concrete was designed and used for the casting of Broad Gauge Pre-tensioned Pre-Stressed Concrete (PSC) sleepers as per Indian Railway Standard Specifications. Pre-tensioning wires of standard High Tensile Strength wire (HTS) were used with a pre-tensioning force of 50kN. Compaction was achieved through table vibrators and steam curing was adopted as per the standard manufacturing process of Indian Railways. The cured concrete sleepers were tested in the lab by stimulating the actual load transfer condones in the field called Rail Seat Centre Bottom (RSCB). Moment of Resistance (MR) and Moment of Failure (MF) of the sleeper was determined for either sides of the sleeper for a loading up to 230kN (MR) and 370kN (MF) as per the standard static bending test procedure. The test results proved that the Geopolymer concrete sleeper has high yield load and high ultimate load.